GOG 244 - The LymphEdema and Gynecologic cancer (LEG) study: The association between the gynecologic cancer lymphedema questionnaire (GCLQ) and lymphedema of the lower extremity (LLE) - Carter, Jeanne (Gynecol Oncol, 2019)
OBJECTIVE: To explore whether patient-reported lymphedema-related symptoms, as measured by the Gynecologic Cancer Lymphedema Questionnaire (GCLQ), are associated with a patient-reported diagnosis of lymphedema of the lower extremity (LLE) and limb volume change (LVC) in patients who have undergone radical surgery, including lymphadenectomy, for endometrial, cervical, or vulvar cancer on Gynecologic Oncology Group (GOG) study 244. METHODS: Patients completed the baseline and at least one post-surgery GCLQ and LVC assessment. The 20-item GCLQ measures seven symptom clusters—aching, heaviness, infection-related, numbness, physical functioning, general swelling, and limb swelling. LLE was defined as a patient self-reported LLE diagnosis on the GCLQ. LVC was measured by volume calculations based on circumferential measurements. A linear mixed model was fitted for change in symptom cluster scores and GCLQ total score and adjusted for disease sites and assessment time. RESULTS: Of 987 eligible patients, 894 were evaluable (endometrial, 719; cervical, 136; vulvar, 39). Of these, 14% reported an LLE diagnosis (endometrial, 11%; cervical, 18%; vulvar, 38%). Significantly more patients diagnosed versus not diagnosed with LLE reported ≥4-point increase from baseline on the GCLQ total score (p < 0.001). Changes from baseline were significantly larger on all GCLQ symptom cluster scores in patients with LLE compared to those without LLE. An LVC increment of >10% was significantly associated with reported general swelling (p < 0.001), heaviness (p = 0.005), infection-related symptoms (p = 0.002), and physical function (p = 0.006). CONCLUSIONS: Patient-reported symptoms, as measured by the GCLQ, discerned those with and without a patient-reported LLE diagnosis and demonstrated predictive value. The GCLQ combined with LVC may enhance our ability to identify LLE.